Improving the Quality of Education in Rural Areas Through Community Service - Listrianti, Feriska; Tomi Apra Santosa; Via Yustitia; Baktiar Nasution; Aat Ruchiat Nugraha; Diah Fatma Sjoraida (eScience Humanity Journal, 2024)
The gap in the quality of education between urban and rural areas is still an important issue. This study aims to determine the effectiveness of community service programs in improving the quality of education in rural areas. This research is a type of qualitative research. The research sample consisted of teachers, students and the community. Programs implemented include teacher training, provision of learning resources, and extracurricular activities designed to increase student and community engagement. The results of the study show that the development of community service programs is effective in supporting the improvement of the quality of education in rural areas. These findings support the use of community service as an effective strategy to strengthen education in remote areas and provide recommendations for policymakers to adopt a similar approach in advancing village education.